2019
DOI: 10.1038/s41550-019-0763-6
|View full text |Cite
|
Sign up to set email alerts
|

Rotational disruption of dust grains by radiative torques in strong radiation fields

Abstract: Massive stars, supernovae, and kilonovae are among the most luminous radiation sources in the universe. Observations usually show near-to mid-infrared (NIR-MIR, λ ∼ 1 − 5 µm) emission excess from H II regions around young massive star clusters (YMSCs). Early phase observations in optical to NIR wavelengths of type Ia supernovae also reveal unusual properties of dust extinction and dust polarization. The popular explanation for such NIR-MIR excess and unusual dust properties is the predominance of small grains … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 79 publications
4
120
0
Order By: Relevance
“…Indeed, according to the RAT theory, anisotropic radiation from stars embedded in high-column density clumps increases the efficiency of grain alignment (Lazarian & Hoang 2007;Lee et al 2020;Hoang et al 2020), which may result in the observed shallower slopes (see also Pattle et al 2019). Moreover, Hoang et al (2019) showed that when the intensity of the radiation from the embedded stars is large, the polarization fraction decreases due to the removal of large grains. We may be witnessing this effect towards the core-hubs (red data points in Fig.…”
Section: Impact Of the Star Formation Feedback On The Observed Polarimentioning
confidence: 99%
“…Indeed, according to the RAT theory, anisotropic radiation from stars embedded in high-column density clumps increases the efficiency of grain alignment (Lazarian & Hoang 2007;Lee et al 2020;Hoang et al 2020), which may result in the observed shallower slopes (see also Pattle et al 2019). Moreover, Hoang et al (2019) showed that when the intensity of the radiation from the embedded stars is large, the polarization fraction decreases due to the removal of large grains. We may be witnessing this effect towards the core-hubs (red data points in Fig.…”
Section: Impact Of the Star Formation Feedback On The Observed Polarimentioning
confidence: 99%
“…It is, however, not yet clear how one could identify the occurrence of this new dust grain alignment mechanism in the objects we study here. In addition, the dust grain size distribution may be affected by RAdiative Torque Disruption (RATD; Hoang et al 2019;Hoang & Tram 2020), which predicts that the dust-grain size distribution will shift to smaller values due to the disruption of large aggregates that are spun-up to suprathermal rotation speeds and thus broken apart by radiative torques.…”
Section: Other Grain Alignment Mechanismsmentioning
confidence: 99%
“…The tensile strength of a dust grain depends on material properties, such as composition and crystallinity. Although the tensile strength of cosmic dust particles is highly uncertain, laboratory measurements gives us an estimate (see Hoang et al 2019, for a summary of tensile strength). The tensile strength of graphite (polycrystalline) is suggested to be aboutŜ max,9 = 0.5 − 1 (Burke & Silk 1974).…”
Section: Coulomb Explosionmentioning
confidence: 99%